Impact of The Use of Plastic Shade on Microclimate Profiles on Potato Cultivation of Seeds (Solanum tuberosum L) of Granola Group G0 Varieties - Ardika, I Putu Tantra; Setiyo, Yohanes; Sumiyati, Sumiyati (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
The purpose of this study was to (1) determine the microclimate profile of plastic shade with different plastic colors and (2) find out the color of plastic for the appropriate shade to increase the quality of granola G0 potato varieties. This study used a completely randomized design, each consisting of four treatments and three replications, namely treatment without shade, transparent plastic shade treatment, blue plastic shade treatment and red plastic shade treatment. For microclimate measurement, the temperature and humidity meter and light meter are used. Microclimate measurement is done once a week, which is at 12.00 p.m. Analysis of sunlight intensity data was carried out to make profile image in the shade using metose contour lines, while the results of measurements of air temperature, soil temperature, humidity and quality variables obtained were processed using a Microsoft Excel computer program to obta in graphics, then analyzed using the deskiptive method and continued the analysis using variance analysis (ANOVA). The result of the intensity of sunlight is made profile countur, and the result of measurement of air temperature, soild temperature, moisture and variable quality is made graph.The results of the study of solar light intensity show the contour of the profile when the plant is two weeks old, the clear shade distribution profile is 975-1025 lux, the shade is read 675-725 lux, the shade is blue 575-595 lux, while in the eight week old plant, the clear shade is 100-800 lux, the shade is red 100-700 lux, and the shade is blue 100-400 lux. Average air temperature without shade 26,2 0C, clear shade 26,8 0C, red shade 26,6 0C, blue shade 26,2 0C, average moisture without shade 76%, clear shade 77%, red shade 78%, and blue shade 79%. The treatment of clear shade shows the best quality, that is an average of 4,4 tubers every single tree, average 257,6 grams every single tree and average of 1 tuber every single tree.